2018
DOI: 10.1111/socf.12439
|View full text |Cite
|
Sign up to set email alerts
|

Exotic Place, White Space: Racialized Volunteer Spaces in Honduras

Abstract: In every year between 2004 and 2012, more than 800,000 Americans reported volunteering internationally (Lough ). These volunteers are overwhelmingly white (McBride and Lough ) and entering a largely nonwhite and developing world. This study starts by questioning how racial status informs volunteer/volunteer tourist interactions, both with locals and with other volunteers, in a global context. In‐depth interviews with 23 missionaries, teachers, and volunteers from the United States and Canada reveal that (1) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Spatial comfort/discomfort is not symmetrical, however, given that Whites, as the dominant race, rule most of the social real estate. Even in spaces they do not dominate, “[Whites] seek out, retreat to, and carve out protected spaces reserved for white use” (Schneider 2018:705). This dynamic pressures people of color to do their best to provide “racial comfort” to Whites even in White-controlled spaces (Robinson 2008).…”
Section: Building Blocks For Theorizing Racialized Emotionsmentioning
confidence: 99%
“…Spatial comfort/discomfort is not symmetrical, however, given that Whites, as the dominant race, rule most of the social real estate. Even in spaces they do not dominate, “[Whites] seek out, retreat to, and carve out protected spaces reserved for white use” (Schneider 2018:705). This dynamic pressures people of color to do their best to provide “racial comfort” to Whites even in White-controlled spaces (Robinson 2008).…”
Section: Building Blocks For Theorizing Racialized Emotionsmentioning
confidence: 99%
“…In the post, there is one black volunteer, whose assumed American nationality and association with Ken necessarily set him apart from local black people. Americans entering largely non-white and developing countries, enter contexts that have been subjected to Western influence with pre-existing understandings of what whiteness and Americanness mean, such as the belief that Westerners are more knowledgeable than locals (Freidus 2017;Schneider, 2018).…”
Section: Post #2mentioning
confidence: 99%
“…For short term missionaries, the spiritual restoration of their authentic self and an improved relationship with God are best accomplished by travelling to impoverished places among the religiously dedicated and joyful poor, with like-minded Christians (Freidus and Caro, 2018). Similarly, Schneider (2018) found that volunteers only expressed a vague desire to help or immerse themselves in a new culture but were more interested in personal growth and escape from their daily routine (p.698). Personal growth leading to a more authentic experience and a more authentic self is sought by volunteers, whether or not their motivation is religious.…”
Section: Authenticity: Of the Self Staged In Tourism And Performed On Social Mediamentioning
confidence: 99%
“…While their initial impressions of place might be invalidated, this invalidation reaffirms faith in new discoveries, leading to statements about “what [the place] was ‘like’, rather than allowing questions of ‘what we did not know’” (p. 222). Additionally, volunteers often create enclavic spaces to separate themselves from the wider community (Schneider, 2018). Even when volunteers are based in rural areas, far from the enclaves, there are still many barriers to connecting with locals, as research from Namibia just after independence describes:volunteers drove around huge airconditioned 4WDs with American flags and “USAID” on the sides.…”
Section: Geographical Imaginaries and International Volunteeringmentioning
confidence: 99%